2009
DOI: 10.1038/jp.2009.187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of instrumental dead space reduction during weaning from synchronized ventilation in preterm infants

Abstract: Objective: A majority of the modalities of synchronized ventilation in preterm infants require the use of flow sensors that can increase dead space and may adversely affect ventilator weaning. The objective of this study was to assess the effects of flow sensor dead space during synchronized intermittent mandatory ventilation (SIMV) weaning in preterm infants.Study Design: Twelve preterm infants (gestational age 25±2 weeks, birth weight 705 ± 158 g, age: 31 ± 186 days, SIMV rate: 25 ± 8 breaths min -1 , peak i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…7 The benefits of reducing instrumental dead space or mitigating its effects are well-recognized and discussed in the literature. 8,9 Multiple approaches to reduce instrumental dead space and/or its effects on patients have been proposed; 3,[8][9][10][11][12][13][14][15] these suggestions even include using lung assist with extracorporeal CO 2 removal. 16 However, trimming the endotracheal tube (ETT) seems to be the only widely accepted method.…”
Section: Introductionmentioning
confidence: 99%
“…7 The benefits of reducing instrumental dead space or mitigating its effects are well-recognized and discussed in the literature. 8,9 Multiple approaches to reduce instrumental dead space and/or its effects on patients have been proposed; 3,[8][9][10][11][12][13][14][15] these suggestions even include using lung assist with extracorporeal CO 2 removal. 16 However, trimming the endotracheal tube (ETT) seems to be the only widely accepted method.…”
Section: Introductionmentioning
confidence: 99%
“…This was clearly shown by an increased diaphragmatic activity as well as significant changes in neural breathing variability during the trial. Although, it is well known that the presence of an ETT and ventilator apparatus increase dead space and respiratory resistance, 38 , 39 the response of extremely preterm infants to this challenge has not been well outlined. It was also interesting to note that the ability to mount such respiratory effort occurred in response to a quite short trial.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated when the dead space in ETT connectors was decreased artificial lung ventilation improved, even though a slight increase in airway resistance and work of breathing occurred (6). Authors commented on this conflicting finding as the increase in resistance and work of breathing may affect patients especially during weaning as the importance of reduction in the instrumental dead space during weaning was previously emphasized (9).…”
Section: Discussionmentioning
confidence: 99%